Libertino patre nati - Ehlers, Widu-Wolfgang (Hyperboreus, 2015)
Horace’s famous phrase libertino patre natum was not coined by Horace, but is taken from historians writing about the life and manners of another freedman’s son, the aedilis curulis of 304 BC, Cn. Flavius Anni f. The earliest testimony can be found in L. Calpurnius Piso Frugi and is then repeated several times up to Livy and Valerius Maximus. Strong parallels between Flavius and Horace contrast with decisive differences: by these words Horace aims to be compared with Flavius and the exemplary picture Flavius left in history. Contrary to Flavius, Horace primis urbis belli domique placuit, at ﬁrst Octavianus’ enemies in the Civil war, then Augustus a few years later.